1956
DOI: 10.1139/v56-079
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Preparing Hydroxyethyl Ethers of Glucose

Abstract: Three monosubstituted hydroxyethyl ethers of D-glucoSe have been synthesized by a novel method involving reduction of the corresponding carboxymethyl derivatives with lithium aluminum hydride. This technique also allowed introduction for the first time of hydroxyethyl substituents containing polyethyle~le oxide chain5 of a definite length in the glucose molec~~le, as exemplified by the synthesis of 3-0-hydroxyethoxyethyl-D-glucose.T h e quantitative paper chromatographic technique has recently been applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1967
1967
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…The results of thin-layer chromatography confirmed that the substitution occurred predominantly at C2. These findings agreed with the work of Shyluk and Time11 [15].…”
Section: Periodate Oxidation Of Native and Etherified Starchessupporting
confidence: 93%
See 1 more Smart Citation
“…The results of thin-layer chromatography confirmed that the substitution occurred predominantly at C2. These findings agreed with the work of Shyluk and Time11 [15].…”
Section: Periodate Oxidation Of Native and Etherified Starchessupporting
confidence: 93%
“…Owing to the unavailability of authentic samples of hydroxyethyl-D-glucose derivatives, some of the located spots in front of those of glucose on the chromatogram plates were isolated, dissolved in water and examined polarimetrically. An initial value of [a];' + 25 was obtained after 2 min and the final value was [a];' = + 47, after 2 h. This was in good agreement with the results found by Shyluk and Time11 [15] for 2-0hydroxyethyl-glucose.…”
Section: Degree Of Substitution Of Hydroxyethyl Starchsupporting
confidence: 90%
“…In brief, after hydrolysis of HES to the oligomeric glucose units by sulfuric acid these were separated by HPLC with refractive index (RI) detection. The peak identification data of the literature were confirmed by independently synthesized samples according to literature of hydroxyethyl glucoses 15,16 . In contrary to the assumption of Ferber, 14 the response factor of 1,2‐O‐ethylenglucose was different from those of the other mono‐ and di‐substituted hydroxyethyl glucose isomers, as was shown by measurement of the independently synthesized sample of 1,2‐O‐ethylenglucose.…”
Section: Methodsmentioning
confidence: 75%
“…The peak identification data of the literature were confirmed by independently synthesized samples according to literature of hydroxyethyl glucoses. 15,16 In contrary to the assumption of Ferber, 14 the response factor of 1,2-O-ethylenglucose was different from those of the other mono-and di-substituted hydroxyethyl glucose isomers, as was shown by measurement of the independently synthesized sample of 1,2-O-ethylenglucose. For all other isomers the response factors were identical and equal to the one of unsubstituted glucose.…”
Section: Molar Substitution Degree Of Substitution and C2/c6 Substitmentioning
confidence: 76%
“…Three solvent systems were commonly used: Both solvent systems (A) and vS) were utilized in the ascending technique at 65*C (115). Descending paper chromatography was performed by solvent systems (C) at room temperature (93,94). Alkaline AgNO^ was used in the detection of the reducing carbohydrates (116).…”
Section: Paper Chromato Graphymentioning
confidence: 99%